Pengelolaan Guest House di Ubud Bali sebagai Pengembangan Nomadic Tourism - I Made Astrama; I Made Darsana (Journal on Education, 2023)
The existence of the Covid-19 pandemic has changed the current tourism trend, namely the workcation trend where tourists work while traveling. One alternative tourism that follows the current trend is nomadic tourism. Lodging is a potential tourism sector that needs to be developed into nomadic tourism, considering that digital nomad tourists have a long time to stay and stay in lodgings, this sector is felt to be able to boost tourism sector income. Therefore, this study aims to describe the management of lodging in Ubud Bali as the development of nomadic tourism. This research is a descriptive qualitative research with data collection techniques through literature studies and then processed with qualitative data analysis techniques. The results of this study concluded that the management of inns in Ubud Bali already contains components of nomadic tourism. However, there are several components that still need improvement, namely the management of the nomadic tourism attraction component and nomadic tourism amenities, while the management of the nomadic tourism access component has been going well. This research is expected to be a recommendation material for lodging managers to find components for the development of nomadic tourism which still need to be improved.